Kegiatan Deteksi Dini Penyakit Diabetes Mellitus Tipe 2 melalui Pemeriksaan Gula Darah Sewaktu pada Kelompok Usia Produktif - Singh, Arwinder; Destra, Edwin; Kurniawan, Junius; Suros, Angel Sharon; Febriastuti, Abebi; Sitorus, Ribka Angeline Hariesti (Jurnal Pengabdian Masyarakat, 2024)
Diabetes mellitus (DM) occurs when blood sugar (glucose) levels are very high for a long period of time. If the glucose level is less than 126 mg/dL during fasting or less than 200 mg/dL two hours after eating, we diagnose diabetes. In low- and middle-income countries, DM affects as many as 422 million people and is one of the leading causes of death worldwide. Uncontrolled diabetes can cause severe complications such as cardiovascular disease, kidney damage, nerve damage, and vision problems. To prevent this complication, early detection through blood glucose checks is critical. This activity uses the PDCA (Plan-Do-Check-Act) method for diabetes screening in adults at PT. Narindo, North Jakarta. The results of blood sugar checks showed that 5 people (3.97%) had blood sugar levels above normal. Increasing public awareness and knowledge about the risks of diabetes and healthy living is very important to reduce the incidence of diabetes so that it can improve overall health outcomes.